Community empowerment through solid waste management using takakura and composting in Huta Gugung village, Sumbul district Dairi province of North Sumatera - Panjaitan, Arifa Masyitah; Indirawati, Sri Malem (Talenta Publisher, 2019)
Garbage is now a global problem facing the world. Indonesia is also one of the biggest contributors to waste in the world. Garbage is goods that are considered to be unused and discarded by the previous owner / user, but for some people can still be used if managed with the correct procedures (Panji Nugroho, 2013). Garbage accumulation is caused by several factors, including a very large volume of waste but there is no capacity for landfills in the village. According to Slamet (2004), both quality and quantity of waste is highly influenced by various activities and living standards of the community. Some important factors include: Population, Socio-economic conditions, Technological Progress, Education level. The waste problem includes 3 parts, namely downstream, process and upstream. In the downstream, waste disposal continues to increase.